Development of Hard Skills, Soft Skills and Organizational Commitments as Intervening Variables Towards Professionalism Performance of Bumdes, Anculai Eco Tourism, Teluk Sebong District, Bintan District - Nurhasanah; Suparjono (Kusuma Negara Business School, 2020)
This study aims to determine the effect of partial, simultaneous and direct and indirect effects on the development of hard skills and soft skills on the professionalism of BUMDes Village in Ekang Anculai through organizational commitment as an intervening variable. This research is categorized as quantitative research because it uses a questionnaire as a research instrument which is the primary data in this study. The sample used in this study amounted to 30 respondents. The collected data was tested and analyzed using the IBM SPSS Statistics 25 program. Based on the results of this study note that hard skills partially significantly influence organizational commitment, soft skills partially significantly influence organizational commitment, hard skills and soft skills simultaneously influence organizational commitment, hard skills have a partial effect on performance professionalism, hard skills have an effect partially on the professionalism of performance, hard skills and soft skills simultaneously influence the performance professionalism, and the path analysis test explains that organizational commitment cannot be a variable mediating between hard skills on performance professionalism and organizational commitment cannot be a variable mediating between hard skills towards professionalism in performance.